Emotional Intelligence - Daniel Goleman (Bloomsbury India, 2013)
Emotional Intelligence Does IQ define our destiny? Daniel Goleman argues that our view of human intelligence is far too narrow, and that our emotions play a major role in thought, decision making and individual success. Self-awareness, impulse control, persistence, motivation, empathy and social deftness are all qualities that mark people who excel: whose relationships flourish, who are stars in the workplace. With new insights into the brain architecture underlying emotion and rationality, Goleman shows precisely how emotional intelligence can be nurtured and strengthened in all of us. Working with Emotional Intelligence Do you want to be more successful at work? Do you want to improve your chances of promotion? Do you want to get on better with your colleagues? Daniel Goleman draws on unparalleled access to business leaders around the world and the thorough research that is his trademark. He demonstrates that emotional intelligence at work matters twice as much as cognitive abilities such as IQ or technical expertise in this inspiring sequel.